Etiologija ekološke kriminalitete v vojaški organizaciji - Grčar, Silvo (Varstvoslovje, 2022)
Purpose: The issue of environmental harm caused by the armed forces in peacetime and wartime is the subject of study in sociology, health, ecology, criminology and other sciences. Although the problem is also recognized by green criminologists, there are fewer contributions from authors who would more comprehensively analyze specific perpetrators of environmental crime, such as the armed forces. We introduce the criminogenic potential of the military institution and etiology of the environmental crime in military institution. Design/Methods/Approach: Analysis of existing book and electronic resources in the field of green criminology, environmental crime and military sociology. We used a descriptive method, a deduction method and a compilation method to describe the content area and place it in the context of green criminology. Findings: Environmental crime is one of the manifestations of crime in a military organization. The military institutional environment creates, maintains or prevents circumstances that generate general and specific forms of crime, including environmental crime, which is caused by the armed forces. Originality/Value: With this paper, we presented the criminogenic nature of a military organization. We have described selected manifestations of environmental crime and criminogenic predisposition of the armed forces to perpetrate environmental crime. The scientific study of the peacetime activities of the armed forces in the context of green criminology represents a novelty and also a contribution to the existing knowledge in the field of (green) criminology and military sociology.
Keywords: armed forces; ekološka kriminaliteta; ekološka kriminologija; environmental crime; environmental harm; green criminology; military; military criminology; military organization; military sociology; oborožene sile; okoljska škoda; vojaška kriminologija; vojaška kultura; vojaška organizacija; vojaška sociologija; vojska